Hydroxynorketamine Blocks N-Methyl-d-Aspartate Receptor Currents by Binding to Closed Receptors - Abbott, Jamie A.; Popescu, Gabriela K. (Molecular pharmacology, 2020)
Ketamine, a dissociative anesthetic, is experiencing a clinical resurgence as a fast-acting antidepressant. In the central nervous system, ketamine acts primarily by blocking NMDA receptor currents. Although it is generally safe in a clinical setting, it can be addictive, and several of its derivatives are being investigated as preferable alternatives. 2R,6R-Hydroxynorketamine (HNK), a ketamine metabolite, reproduces some of the therapeutic effects of ketamine and appears to lack abuse liability. Here, we report a systematic investigation of the effects of HNK on macroscopic responses elicited from recombinant NMDA receptors expressed in human embryonic kidney 293 cells. We found that, like ketamine, HNK reduced NMDA receptor currents in a dose-, pH-, and voltage-dependent manner. Relative to ketamine, it had 100-fold-lower potency (46 µM at pH 7.2), 10-fold-slower inhibition onset, slower apparent dissociation rate, weaker voltage dependence, and complete competition by magnesium. Notably, HNK inhibition was fully effective when applied to resting receptors. These results revealed unexpected properties of hydroxynorketamine that warrant its further investigation as a possible therapeutic in pathologies associated with NMDA receptor dysfunction. NMDA receptors are excitatory ion channels with fundamental roles in synaptic transmission and plasticity, and their dysfunction associates with severe neuropsychiatric disorders. 2R,6R-Hydroxynorketamine, a metabolite of ketamine, mimics some of the neuroactive properties of ketamine and may lack its abuse liability. Results show that 2R,6R-hydroxynorketamine blocks NMDA receptor currents with low affinity and weak voltage dependence and is effective when applied to resting receptors. These properties highlight its effectiveness to a subset of NMDA receptor responses and recommend it for further investigation.